Sentiment Lexicon - Språkbanken Text (University of Gothenburg, 2024)
Please reference the lexicon using the following reference:

Nusko, Bianka and Tahmasebi, Nina and Mogren, Olof. 2016. Building a Sentiment Lexicon for Swedish

Vänligen använd följande artikel som referens för lexikonet:

Nusko, Bianka and Tahmasebi, Nina and Mogren, Olof. 2016. Building a Sentiment Lexicon for Swedish
Sentimentlexikon
Keywords: Language Technology (Computational Linguistics); lexicon; Natural Language Processing; Språkbehandling och datorlingvistik